Agricultural potential of Brazilian cerrado - Goedert, Wenceslau J.; Lobato, Edson; Wagner, Elmar (Pesquisa Agropecuaria Brasileira, 2014)
The agriculture in Cerrado Region has shown great improvement. Research and farmer experiences, accumulated in the last decade, reveal a great potential to be explored. On the other hand, the increasing world food deficit is well known mainly due to the accelerated world population growth. Therefore, it is not difficult to predict the important role of Brazilian savanna region, not only to Brazil but to the rest of the world as well. In this paper, projections are made on the ammount of grain and energy that this region can produce as well as strategies and requirements for this potential to become a reality.